2020
DOI: 10.1021/acsomega.0c02825
|View full text |Cite
|
Sign up to set email alerts
|

On the Second Explosion Limits of Hydrogen, Methane, Ethane, and Propane

Abstract: In this work, we have first investigated the explosion limit behaviors from hydrogen to propane through numerical simulations and validated with the available experimental data. The shape of the explosion limit curves and the possible turning points ( P 1–2 , T 1–2 ), first to second limit transition, and ( P 2–3 , T 2–3 ), second to third limit transition that bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…If N 2 had been chosen as inert diluent, a minimum of 46 mol % would have been needed in the mixture for ethane to reach FIP at ambient conditions. 27 Given the different capacity to reduce flammability between N 2 and H 2 O, 24 a high % of H 2 O as diluent was chosen to stay above the FIP.…”
Section: Market Assessment and Design Basismentioning
confidence: 99%
“…If N 2 had been chosen as inert diluent, a minimum of 46 mol % would have been needed in the mixture for ethane to reach FIP at ambient conditions. 27 Given the different capacity to reduce flammability between N 2 and H 2 O, 24 a high % of H 2 O as diluent was chosen to stay above the FIP.…”
Section: Market Assessment and Design Basismentioning
confidence: 99%
“…While bringing convenience to people, natural gas also poses greater safety risks. In recent years, some natural gas explosion accidents have occurred frequently, causing serious casualties and social and economic losses. At present, there are more studies on the combustion and explosion problems in the safe transportation process of large aspect ratio pipelines, concentrating on the study of the influence of characteristic parameters such as pressure relief ratio, opening pressure, opening time, and blocking ratio on the natural gas-constrained explosion process, and it was found that when the blockage ratio is set reasonably, the power generated by the explosion can be effectively reduced. Given this, how to scientifically and effectively set the shape of the vent, the blockage ratio and opening position, and other characteristic parameters have become the focus of research by many scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accidental leakage and improper handling during the production, processing, storage, and transportation of methane can result in the formation of complex combustible gas mixtures. Once the explosion conditions are satisfied, the gas explosion can cause serious property damage and casualties. To prevent and control gas explosion accidents, effective measures need to be found to minimize the scope and intensity of gas explosion. Inert gases are often used as inhibitors of methane-air explosions.…”
Section: Introductionmentioning
confidence: 99%